"Igra boga" kao jedan od aspekata intertekstualnosti u Faulsovom romanu "Čarobnjak" (Philologia, 2021)
There are numerous examples of intertextuality in John Fowles's novel The Magus. One of the most remarkable is the godgame. John Fowles uses the term godgame to depict the game that the protagonist imposes upon one or more of his fellow-characters. Such a character, the "god", abducts the powers of God. The concept of the godgame was first used in Charles Dickens's novel Great Expectations. The postmodern novel The Maggus makes use of the same pattern as the Victorian novel Great Expectations. This paper deals with the consequences of the godgame in different novelistic traditions: Victorian and post-modern, respectively.